The Influence of Product, Price, Brand Image, Promotion and Purchase Decision: Buyers of Kahf Products in Langsa City - Andi Peristiawan; Ulya, Zikriatul; Agustinar; Zulfa Eliza (JIM: Jurnal Ilmiah Mahasiswa, 2025)
Purchasing decision is an action taken by consumers to make a product purchase, so the manufacturer tries will meet the needs of the consumer want. Therefore, producers create a variety of varied products and various choices of products themselves such as KAHF products. KAHF products have a variety of product variants, for example skincare products are specifically made as skincare for men. The KAHF product still has shortcomings of its products at an inappropriate price and a brand image that is not widely known and the promotion of the KAHF product. For this reason, this study aims to find out the influence of products, prices, brand images and promotions on KAHF product purchasing decisions in Langsa City. This type of research is descriptive quantitative. The technique used is simple random side using the slovin formula with the number of samples, 100 respondents. Data collection using questionnaires or questionnaires by testing multiple linear regression analysis using IBM Statistic 22. The results showed that the results of partial test (t-test) product variables affect the decision of the purchase of Kahf products by 41.7%, price variables affect the decision of the purchase KAHF products are 52.2%, brand image affects the decision of the purchase of KAHF products by 52.3%, and promotion affects the decision of the purchase of KAHF products by 18.9%. Simultaneous test results (F-test) shows the product, price, brand image, and promotion get a calculated Fvalue of 24,468 > Ftable value of 2.46, which means simultaneously affecting the purchasing decision of KAHF products in Langsa City.